(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Today, almost all regions of the world are governed by knowledge and intelligence. Today humanity is very advanced in science and education. In our information age, the prestige of intellectual professions is growing. Bringing a person to this potential, realizing his intellectual potential is the most important task of the education system. However, countries around the world see that the economies of countries with underdeveloped education are also underdeveloped. Today it is impossible to educate modern personnel without the introduction of a modern education system. The synergetic methodology is an important area that contributes to integrated education, which can become the basis of modern education based on a systems approach. The problem of a systems approach to modern education, promoted in the article, focuses on interdisciplinary integration, critical and logical thinking as part of synergistic education. This is an approach that corresponds to modern education, proving that it is constantly evolving, tirelessly working on itself and that stagnation in the learning process is unacceptable.